Obesity management in primary care: A joint clinical perspective and expert review from the Obesity Medicine Association (OMA) and the American College of Osteopathic Family Physicians (ACOFP) - 2025 - Nicholas Pennings; Catherine Varney; Shaun Hines; Bernadette Riley; Patricia Happel; Samir Patel; Harold Edward Bays (Obesity Pillars)
Background: This collaboration from the Obesity Medicine Association (OMA) and the American College of Osteopathic Family Physicians (ACOFP) examines obesity management from a primary care perspective. Methods: This joint perspective is based upon scientific evidence, clinical experience of the authors, and peer review by the OMA and ACOFP leadership. The goal is to identify and answer sentinel questions about obesity management from a primary care perspective, utilizing evidence-based publications, and guided by expert clinical experience. Results: Obesity is a disease that contributes to both biomechanical complications and the most common cardiometabolic abnormalities encountered in primary care. Barriers that impede optimal care of patients with obesity in primary care include failure to recognize obesity as a disease, lack of accurate diagnosis, insufficient access to obesity treatment resources, inadequate training, insufficient time, lack of adequate reimbursement and the adverse impact of bias, stigma, and discrimination. Conclusions: Family physicians are often the first line of treatment in the healthcare setting. This affords early intervention opportunities to prevent and/or treat overweight and/or obesity. Patient care is enhanced when primary care clinicians recognize the risks and benefits of anti-obesity medications and bariatric procedures, as well as long-term follow-up. Practical tools regarding the 4 pillars of nutrition therapy, physical activity, behavior modification, and medical interventions (anti-obesity medications and bariatric surgery) may assist primary care clinicians improve the health and lives of patients living with obesity.